Influence of egg age of Helicoverpa zea (Boddie) on the parasitism by Trichogramma pretiosum Riley - Pratissoli, Dirceu; Oliveira, Harley Nonato de (Pesquisa Agropecuaria Brasileira, 1999)
Among the agents of biological control, the parasitoids of the genus Trichogramma represent one of the most important groups, as they are able to control many pests in agriculture. The objective of this work was to determine the best age of the Helicoverpa zea (Boddie) eggs so that the Trichogramma pretiosum Riley could have the best efficiency against this pest. One, two, three and four-days-old eggs were offered for the parasitism during 24 hours, at 25 ± 1ºC, relative humidity 70 ± 10% and photofase of 14 hours. One-day-old eggs showed the highest rates of parasitism, viability, and number of descendants for each female. The highest efficiency with T. pretiosum will be reached in the field conditions, when observed a great density of H. zea eggs until two days of embryonic development.